Transarticular tibiotalocalcaneal nailing versus open reduction and internal fixation for treatment of the elderly ankle fracture: protocol for a multicentre, prospective, randomised controlled trial. Issue 1 (21st January 2019) - Tuckett, Paul; Hope, Matthew; Tetsworth, Kevin; Van De Pol, Jerry; McDougall, Catherine
Abstract : Introduction: Ankle fractures are common in the elderly population. Surgical fixation is technically challenging and often results in complications due to high rates of osteoporosis and vascular disease. Open reduction and internal fixation (ORIF) often requires prolonged periods of non-weight bearing increasing the risks of complications. Tibiotalocalcaneal (TTC) nailing has been suggested as an alternative to ORIF which allows immediate weight bearing, and is suggested to result in fewer complications. This study aims to compare the two surgical techniques in the elderly population with ankle fractures. Methods and analysis: The study will be a multicentre, prospective, randomised controlled trial comparing ORIF to TTC nailing in 110 patients with ankle fractures aged 50 or above with a Charlson Comorbidity Index of greater than or equal to four. Participants and assessors will not be blinded to intervention. The primary outcome measure will be overall complication rate. Secondary outcomes include length of hospital stay, mobility at discharge, discharge destination, the American Orthopaedic Foot and Ankle Society Ankle-Hindfoot score, the Olerud-Molander Ankle Score, mortality rate, rate of secondary surgical interventions and number of blood transfusions required postoperatively. Our null hypothesis is that there is no clinically significant difference in the primary outcome measure between the two treatment groups. Ethics and dissemination: The study has been approved by Metro South Hospital and Health Services Human Research Ethics Committee (EC00167) (reference number HREC/17/QPAH/351). Discussion: Completion of this trial will provide evidence on the effectiveness of TTC nailing versus ORIF in treatment of the elderly ankle fracture. If TTC nailing is found to result in superior outcomes, this trial has the capacity to change current clinical practice. Trial registration number: ACTRN12617001588381;Pre-results andU1111-1203-1704.